Descriptive analysis of the integrative curriculum of smp islam terpadu wahdah islamiyah makassar - Syamsuar Hamka (Balai Diklat Keagamaan Ambon, 2023)
This study examines the formulation of problem 1). What is the profile of this school, and 2). What is the pattern of integration of the curriculum? The approach used is descriptive-qualitative, with interview, observation, and documentation methods. The results of this study indicate 1) SMP Islam Terpadu Wahdah Islamiyah Makassar has the vision to produce alumni who have good morals and have achievements in the field of Islam and science based on the Qur'an and as-Sunnah. 2) The curriculum structure of SMP Islam Terpadu Wahdah Islamiyah Makassar includes the substance of lessons taken at one level for three years by combining the curriculum of the education service and the curriculum of Islamic content.